Potential benefits of integrating teaching and learning technologies into higher education pedagogies : a scoping review - Thabane, Lerato (African Perspectives of Research in Teaching & Learning (APORTAL), 2025)
The integration of digital technologies into higher education has gained momentum due to global shifts in pedagogy and learning environments. Understanding the benefits of this integration is essential for informing institutional strategies and enhancing teaching practices. This scoping review aims to identify and synthesise the potential benefits of teaching and learning technologies within higher education contexts. Guided by Arksey and O’Malley’s (2005) framework, a systematic search of literature published between 2018 and 2023 was conducted across ten peer-reviewed journals. Thematic analysis, following Braun and Clarke’s (2006) approach, was employed to extract and categorise key findings. Nineteen studies met the predefined inclusion criteria. Five key benefits were identified: (1) unrestricted access to educational materials; (2) increased student engagement and promotion of active learning; (3) enhanced student learning and improved academic success; (4) improved communication through collaborative learning; and (5) enhanced quality of teaching and learning. The review highlights the significant potential impact of digital technologies in higher education, while also emphasising the need for a more comprehensive theoretical engagement and broader literature coverage. Noted limitations include the scope of journal selection and reporting focus. These findings offer valuable insights for informing future pedagogical strategies and guiding further research.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 7, Volume 9, 2025 Special Issue
Keywords: Technologies; Teaching and learning; Scoping review; Pedagogies; Higher education; Benefits; Education higher, South Africa; Computer-assisted instruction; Educational technology